VCs' decision processes - Shepherd, Dean A.; Zacharakis, Andrew; Baron, Robert A. (Journal of Business Venturing, 2003)
Decision-making processes employed by venture capitalists (VCs) varying in experience were compared. Results show that for relatively inexperienced VCs, increasing experience is associated with improvements in reliability and performance relative to a benchmark (a bootstrapping model). Beyond a specific point, however, further gains in experience are associated with actual reductions in reliability and performance. Thus, greater experience at the venture capital task may not always result in better decisions.